Who is responsible for protecting my health during the COVID- 19 pandemic? (Alternate Horizons, 2021)
Since the report of the first COVID-19 infected person in South Africa, COVID-19 moved from being a distant threat to a new reality overnight. Metaphorically, COVID-19 could be described as rain, and in order to be protected, one would need to stand under an umbrella. The fundamental question that stems from this is who is holding this protective umbrella? Is the government holding the umbrella or are we holding the umbrella? In this article/ commentary/perspective, we briefly discuss the responsibility of the South African government and the individual during this global pandemic, the reasoning behind the implementation of lockdown and the consequences thereof. We conclude that both government and citizens need to cooperatively take responsibility and work together to fight COVID-19. The protective umbrella needs to be held by both governments and by ourselves.
Keywords: COVID-19; health; South Africa; opinion